An experimental study on reshaping C110 deformed casing with spinning casing swage - Yuanhua Lin; Kuanhai Deng; Dezhi Zeng; Qining Zhao; Mule Wang; Yiyi Kang (Natural Gas Industry B, 2015)
Casing deformation affects the implementation of stimulation and development measures of oilfields directly; however, the reshaping force and torque usually are determined by experience when the deformed casing is repaired with the spinning reshaping technology; if the repairing force or torque is too large, it will result in the damage of casing and cement sheath as well as sticking accident. So, the collapse experiments were performed on the YAW-200 pressure testing machine by using one production casing which is often used in the oilfield and then the reshaping test of deformed casing (C110) was performed in turn by using two spinning casing swages of which the diameter is 126 mm and 129 mm respectively. The continuous rotator and thrust bearing were used to provide the torque and reshaping force respectively in the repairing process. The reshaping force and torque required to reshape the deformed casing, the deformation law and the springback value of deformed casing were obtained. Test results show that the diameter differential between the two spinning casing swages is reasonable. Furthermore, in order to ensure the safety and reliability of the implementation of post-production technologies, the mechanical properties of deformed casing before and after reshaping were tested. It was found that all the mechanical parameters of the deformed casing after reshaping reduced, which resulted in the decrease of the strength of the reshaped casing. These research achievements would provide important experimental data in optimizing the structure and construction parameters of spinning casing swages.